EDUKASI TENTANG SELFITIS UNTUK MENURUNKAN KECANDUAN SELFI PADA REMAJA DI RT 002 RW 007 KELURAHAN SEMBUNG KABUPATEN TULUNGAGUNG - risnasari, norma; Aizah, Siti; Wati, Susi Erna; Oktavia, Erika Violin; Nuur, Awin Latifah (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Selfitis is an activity that describes the habit of taking excessive selfies, the uploading them to social media sites. Selfies have become a habit for many people and can indeed fulfill the need for self-actualization. But if done excessively and uncontrollably, the habit of selfie can be a symptom of a mental disorder, in teenagers this can be a time full of social anxiety and depression. Health counseling was held on December 10, 2020 with pre-test and post-test. The results of the pre-test on 15 adolescents, 8 adolescents (53%) said they did not know about meaning of selfitis, 5 adolescents (33,3%) said they did not know the cause of selfitis, 12 adolescents (80%) did not know the signs of selfitis and 10 adolescents (66,7%) did not know the impact of selfiti, and 13 adolescents (86,7 %) did not know about selfisitis treatment. The results of post-test, 15 adolescents (100%) stated that they knew and understood the meaning, causes, and effects of selfitis, while 12 adolescents (80%) stated that they knew and understood the signs and treatment of selfitis. The existence of self-awareness to control the use smartphones wisely is expected to prevent adolescents from falling into the mental disorder selfitis.